Exploring the impact of PFAS exposure and sleep duration on kidney stone formation in the U.S. population - Chen, Jianbai; Zhang, Zhiming; Xu, Gongquan; Tang, Qisheng; Nie, Zhiyong; Qiu, Jianxin; Gao, Xiaoping (Frontiers in Public Health, 2025)
BackgroundPerfluoroalkyl substances (PFAS), including perfluorooctane sulfonate (PFOS), are persistent environmental pollutants with potential nephrotoxic effects. Concurrently, sleep duration has been implicated in metabolic dysregulation, influencing kidney function. While individual studies have examined the effects of PFAS exposure and sleep duration on kidney health, their combined impact on kidney stone formation remains largely unexplored.MethodsWe conducted a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) 2013-2016. PFAS exposure was assessed through serum concentrations of multiple perfluoroalkyl compounds. Sleep duration was self-reported and categorized as <7 h or ≥7 h. Kidney stone status was determined through self-reported medical diagnoses. Multivariable logistic regression models were used to examine associations between PFAS exposure, sleep duration, and kidney stone formation, adjusting for demographic and lifestyle confounders. Non-restrictive cubic spline (RCS) analysis was employed to assess potential non-linear relationships.ResultsAmong 1,263 participants, 551 (43.6%) reported a history of kidney stones. Higher serum concentrations of PFDE, PFHxS n-PFOS, and Sm-PFOS were significantly associated with increased odds of kidney stone formation (p < 0.05). Participants with sleep duration <7 h had a 1.03-fold higher risk of kidney stones (95% CI: 1.01–1.10, p= 0.007). RCS analysis identified non-linear dose-response relationships for several PFAS compounds suggesting threshold effects. Interaction analysis revealed a synergistic effect between PFAS exposure and insufficient sleep, amplifying kidney stone risk.ConclusionOur findings suggest that both PFAS exposure and insufficient sleep independently contribute to kidney stone formation, with evidence of a combined exacerbating effect. These results underscore the importance of addressing environmental exposures and lifestyle factors in kidney stone prevention strategies.